Enrichment of benzo(a)pyrene in milk by saponification-solvent microextraction - Lim, Khai Wei; Khor, Zhi Zhong; Wan Mohd Khalik, Wan Mohd Afiq; Kamaruzaman, Sazlinda (Malaysian Institute of Chemistry, 2024)
Milk carries significant amounts of essential fats and nutrients such as magnesium, calcium and zinc. Hence, they have always been the significant components consumed by all age groups, especially infants and elderly seniors. However, the lipophilic nature of polycyclic aromatic hydrocarbons (PAHs) increases the likelihood of depositing fats within the milk and may result in both acute and chronic adverse health effects for humans. Therefore, a rapid and environmentally friendly saponification-solvent microextraction coupled with high-performance liquid chromatography and fluorescence detection was developed and validated for the determination of benzo(a)pyrene (BAP) in milk samples. BAP was separated by a reversed-phase C18 column with a mobile phase composed of 70% acetonitrile in isocratic mode. The microextraction variables included the type and volume of organic solvent, the effect of salt addition and vortex time were investigated and optimised. Under optimal conditions, the linearity of the method was established in the range of 0.25 to 5 µg L-1 with the correlation of determination = 0.9939. The ultra-trace limit of detection and limit of quantification were obtained as 0.02 and 0.07 µg L-1, respectively. The average of the relative recovery ranged from 73.7-116.0% with relative standard deviations ≤ 7.2%. The saponification-solvent microextraction is green considering its microformat in addition to the selectivity and sensitivity enhanced by saponification. © 2024 Malaysian Institute of Chemistry. All rights reserved.